The Problematics of Unilateral Termination of Employment from the Perspective of Worker Protection - Maria Vianney Lourdes Sugara (Media Hukum Indonesia (MHI), 2026)
Â Termination of employment is a crucial aspect of labor law that directly affects the livelihood of workers. Although it has been regulated under Law Number 13 of 2003 concerning Manpower, as amended by the Job Creation Law, unilateral termination of employment by employers without proper procedures remains prevalent in practice. This study aims to analyze the problems surrounding unilateral termination of employment and to examine the effectiveness of legal protection for workers from a labor law perspective. The research employs a normative juridical method using statutory and conceptual approaches, supported by a literature review of primary, secondary, and tertiary legal materials. The findings indicate that unilateral termination persists due to the imbalance of bargaining power between workers and employers, weak labor supervision, and the ineffectiveness of industrial relations dispute resolution mechanisms. Furthermore, existing legal provisions have not fully ensured optimal protection for workers, particularly in terms of procedural certainty and enforcement of sanctions. As a result, workers are placed in a vulnerable position and lack adequate legal certainty. Therefore, it is necessary to strengthen the legal protection system through clearer regulatory frameworks, enhanced supervision, and simplified dispute resolution mechanisms to ensure the fair and sustainable fulfillment of workersâ€™ rights.